Protection system analysis for power distribution system - Zaw, Hein Htet (2016)
Protection System Analysis for Mesh Power Distribution System is important to achieve the reliability of the power distribution system and protection of the system equipment. Understanding on the relay coordination of the upstream and downstream electrical equipment plays an important role when discriminating the faults zones to protect the equipment. In this project, power transformers, switchgears, motors and protection devices will be analysed in order to get reliable power distribution system. Studied and investigated differential protection, overcurrent protection, line protection and earth fault protection during fault and the design project shall restore the electrical power after clear the fault by supplying from alternative source. Simulated and compared the results by using MATLAB software and analyse waveforms during fault and after cleared the fault.